PENGEMBANGAN E-LEARNING BERBASIS WEBSITE SEBAGAI SUMBER BELAJAR FIKIH MODEL BLENDED LEARNING - Mabruroh, Dewi Azizatul; Faishol, Riza; Muftiyah, Al (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The 50% post-Covid-19 learning system has an impact on limiting the learning process. Blended learning model to meet learning deficiencies. The rapid movement of science and technology, especially in the field of information and communication (ICT), demands that human resources continue to innovate and master technology. Website is one of the flexible e-Learning media for learning. This experiment to develop a website-based e-Learning media as a source of learning Fiqh for class XI Divorce material at MA Negeri 2 Banyuwangi. The method used is the research and development (R&D) model of the ADDIE approach developed by Robert Maribe Branch, there are Analyze, Design, Develop, Implement, and Evaluate. The research instrument is a non-test questionnaire. Data analysis with qualitative descriptive and descriptive statistics. The results of the research from the assessment of the material expert team are 95% very feasible criteria, the media team is 84% ​​very feasible category, 94% media users are very feasible category and 83% field trial is very feasible category. This shows that the e-Learning website is very suitable to be used as a learning resource in learning Fiqh class XI Divorce material.